Unlocking Galactic Mysteries: Relativistic Insight into Orbital Hyper-Speeds and Dark Matter in Gas-Rich Galactic-Halos (Global Journal of Science Frontier Research, 2023)
This study is a novel approach to the cosmological issue of the dark matter effect observed in gas-dominated galaxies in rotation A possible physical mechanism is investigated to produce the hyper orbital-speeds in outer halo parts of galaxies In the galactic space gas clouds are abundant Motion of the gas-clouds is viewed as a flow of a continuous fluid in curved space with gravity Dynamical motions of the space-fluid are studied by Fluid Dynamics extended to the one of a relativistic gravitational field The fluid flow to be studied in relativistic gravity field is reinforced by the fluid gauge theory equipped with a background dark gauge field The stress-energy tensor in the general relativity is revised to take account of intrinsic nature of stress field by generalizing the isotropic pressure to an anisotropic stress field Present study takes a new double-sided approach both dynamically and physically Namely a gauge-field is newly incorporated in the system as a dynamical term and the system is studied under a new mechanism of the anisotropic stress fields